Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter R - Section R.3 - Exponents, Roots, and Order of Operations - R.3 Exercises - Page 28: 1


False, $-7^{6}=-(7^{6})$

Work Step by Step

$-7^{6}=-(7^{6})=-(7\times7\times7\times7\times7\times7)=-(117649)=-117649$ $(-7)^{6}=(-7\times-7\times-7\times-7\times-7\times-7)=117649\ne-117649$ Therefore, we know that $-7^{6}=-(7^{6})$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.